Additive Manufacturing of Zirconia - Llanos, Gustavo (My University, 2018)
The potential of Zirconia for fabrication of components using additive manufacturing technologies extend the application range for this material. There are some limitations with the relatively simple design that can be achieved by conventional manufacturing processes for ceramics. However, there are some challenges to overcome in additive manufacturing of zirconia given the difficulty to obtain fully dense components without defects. In this research, additive manufacturing of Yttria-stabilized zirconia was investigated to increase the overall reliability of a VAT-photopolymerization technique. Powder processing was performed before suspension preparation to study the effect on further steps. An optimum resin composition was developed and printing parameters were adjusted according to the suspension characteristics. Post-processing steps were tested and investigated to analyze the effect on the component and its final properties. Powders with different stabilizing agents using the same resin were tested to evaluate the powder effect on the overall process. The results obtained show that the resin composition developed allows manufacturing of components with Yttria and Magnesia stabilized Zirconia. Powder characteristics such as grain size and surface area showed that they can limit the powders suitable for this technique. Characterization of the components shows uniform microstructure with good dimensional accuracy, allowing to obtain near fully dense components with this technology.
Keywords: Materialteknik; Materials Engineering